Does Early Follow-Up Improve the Outcomes of Sepsis Survivors Discharged to Home Health Care?. Issue 8 (August 2019) - Deb, Partha; Murtaugh, Christopher M.; Bowles, Kathryn H.; Mikkelsen, Mark E.; Khajavi, Hoda Nouri; Moore, Stanley; Barrón, Yolanda; Feldman, Penny H.
Abstract : Background: There is little evidence to guide the care of over a million sepsis survivors following hospital discharge despite high rates of hospital readmission. Objective: We examined whether early home health nursing (first visit within 2 days of hospital discharge and at least 1 additional visit in the first posthospital week) and early physician follow-up (an outpatient visit in the first posthospital week) reduce 30-day readmissions among Medicare sepsis survivors. Design: A pragmatic, comparative effectiveness analysis of Medicare data from 2013 to 2014 using nonlinear instrumental variable analysis. Subjects: Medicare beneficiaries in the 50 states and District of Columbia discharged alive after a sepsis hospitalization and received home health care. Measures: The outcomes, protocol parameters, and control variables were from Medicare administrative and claim files and the home health Outcome and Assessment Information Set (OASIS). The primary outcome was 30-day all-cause hospital readmission. Results: Our sample consisted of 170, 571 mostly non-Hispanic white (82.3%), female (57.5%), older adults (mean age, 76 y) with severe sepsis (86.9%) and a multitude of comorbid conditions and functional limitations. Among them, 44.7% received only the nursing protocol, 11.0% only the medical doctor protocol, 28.1% both protocols, and 16.2% neither. Although neither protocol by itself had a statistically significant effect on readmission, both together reduced the probability of 30-day all-cause readmission by 7 percentage points ( P =0.006; 95% confidence interval=2, 12). Conclusions: Our findings suggest that, together, early postdischarge care by home health and medical providers can reduce hospital readmissions for sepsis survivors. Abstract : Supplemental Digital Content is available in the text.